Health and health literacy from the child's perspective: a qualitative study in 9–12-year olds. - Boxtel, Wieke Van; Chinapaw, Mai; Jerković-Ćosić, Katarina (Health Promotion International, 2025)
To promote health literacy (HL) in children, it is crucial to recognize their unique social environment, experiences, and comprehension of health and HL. This study aims to gain insight into the perspectives of children aged 9–12 years regarding health and HL within the context of health promotion. We conducted focus group discussions with children at three primary schools in the Netherlands, covering (i) What health means to children (ii) How they engage with health information (HL), and (iii) How they respond to the items of an HL questionnaire (HLS-Child-Q15-NL). Thematic analysis was used to analyze data from nine focus groups with 46 children. We identified three themes: (i) perspectives of health and healthy living, (ii) information for healthy living, and (iii) sources of information for healthy living. Children rated being yourself, physical activity, and happiness as the most important health topics. They receive health information passively, mainly from caregivers and social media, and emphasize the need for simple language. Trustworthiness of sources and usefulness of information were also important. Responses to the HLS-Child-Q15-NL varied, with some items being unclear and leading to misunderstandings, though generally seen as easy. The findings highlight children's broad perspective of health and HL. Health-promoting activities should focus on developing HL skills related to children's lived experiences and health topics that they deem important. This will present an opportunity for children to engage with health information more actively and critically.